DETERMINING THE LOCATION AND OPTIMAL NUMBER OF BUILDING LIFTS IN HIGH-RISE CONSTRUCTION PROJECTS USING A LINEAR INTEGER MATHEMATICAL MODEL - M. Jawaheri; M. Ahmadnia; M. Maghrebi; R. Ghanbari (مهندسی عمران شریف)
Vertical transportation technology is essential for constructing tall and medium-rise buildings. Although lifts are a functional component of buildings, their vital nature depends on the continuous and uninterrupted use of lifts in each tall building. Therefore, using lifts for vertical transportation of materials and human resources has gained greater importance. Extensive research has been conducted on reducing lift travel time between floors, optimizing lift systems design, optimizing lift movement paths, determining the sequence of floor travel, managing lift energy consumption, and floor zoning. However, the optimization of lift installation locations and quantities has not been examined so far. The use of lifts in construction projects incurs multiple costs, including rental or purchase costs, energy consumption during vertical transportation of materials, and operator salaries. One of the main solutions to reduce these costs is to minimize the duration of lift usage, which, by delivering the required materials on time, can also reduce the project's execution time. The installation costs of lifts may also vary at different candidate points due to factors such as weight and dimensional capacity, electricity consumption, the number of visits for monthly or annual maintenance and repair, and lift operator salaries. Additionally, some candidate points may have advantages over other points in terms of the amount of horizontal movement of materials on building floors. These distinctive features present challenges in selecting the optimal installation point. In this article, an integer linear programming model has been proposed to determine the optimal number and location of lift installations. The number of lifts used can affect the number of project working days, and as a result, the optimization is performed simultaneously for the number of working days and the number of lifts. The goal of this optimization model is to minimize the duration of lift usage and the associated costs. Additionally, using this model, the number of project working days is obtained with a balanced distribution of lift activities. The effectiveness of the proposed model was tested in a case study to evaluate its effectiveness. The case study involved a 20-story building located in the city of Mashhad, which requires determining the number and location of lifts during the workshop preparation phase. Using this model can lead to cost reduction and a decrease in the number of project working days.